The effect of a diode-pumped solid-state laser with a wavelength of 589 nm on T-lymphocyte proliferation - Marwa Akram Nafe'a,; Nibras Hatim. Khamees,; Mustafa Salih. Al Musawi, (Journal of the Pakistan Medical Association, 2024)
Objective: To assess how low-level laser irradiation affects T cells. Method: The case-control interventional study was conducted from November 2021 to April 2022 after approval by the ethics review committee of the College of Medicine, Mustansiriyah University, Baghdad, Iraq, and comprised healthy individuals. Phlebotomy was used to collect 4ml of blood. A portion of each sample was exposed to 589nm laser radiation, while the other portion was used as a control. The irradiated sample was divided into whole blood and in-plate subgroups. Phytohemagglutinin was used for mitotic stimulation of T-lymphocytes, and cell proliferation assay was used to stimulate T lymphocytes measured using MTS assay (3-(4,5-dimethylthiazol-2-yl)-5- (3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium). Optical density was measured using enzyme-linked immunosorbent assay. Data was analysed using GraphPad prism software. Results: There were 35 subjects, 17(49%) males and 18 (51%) females, with an age range between 19-25 years, all without any disease or medication. Laser irradiation stimulated T-lymphocyte proliferation to levels that depended on the dose of laser used. At energy 30J/cm2 there was a significant increase in the in-plate subgroup of irradiated samples compared to controls and between the two irradiated subgroups (p<0.05). At 50J/cm2 dose, there was a significant increase in the whole blood subgroup compared to the controls (p<0.05). At 70J/cm2 dose, there was a significant difference in the whole blood subgroup compared to the controls, and between the two irradiated subgroups (p<0.05). Conclusion: The stimulation of T lymphocyte proliferation by the application of a 589nm laser could have medical applications in the field of immune system enhancement. Key Words: Phytohemagglutinins, Phlebotomy, Lasers, Lymphocytes, Proliferation, Immunosorbent